Pengaruh Orientasi Pelanggan Terhadap Kinerja Pemasaran Coffee Shop Di Kota Padang Melalui Kapabilitas Penciptaan Nilai Sebagai Variabel Mediasi - Rifa Nabila Syahira; Thamrin Thamrin (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to analyze how customer orientation, value creation capabilities and marketing performance affect coffee shops in Padang city. This research was conducted on 90 coffee shop business actors in Padang city with quantitative research methods. The data of this study were analyzed by using PLS 4, the data processed in this study to examine the relationship between customer orientation, value creation capabilities on marketing performance. This study produces answers that all hypotheses are proposed and shows that customer orientation has a significant positive effect on the performance of coffee shops in the city of Padang. Customer orientation has a positive and significant influence on value creation capabilities. Value creation capability has a positive and significant influence on the marketing performance of coffee shops in Padang city. Customer orientation has a positive and significant effect on the marketing performance of coffee shops in Padang city through value creation capability as a mediating variable.